2019
DOI: 10.4236/psych.2019.104029
|View full text |Cite
|
Sign up to set email alerts
|

Machiavellianism and Intimacy Attitudes in the Interpersonal Relationships

Abstract: The present study investigated the relation between Machiavellianism and intimacy attitudes in the interpersonal relationships. Male (N = 46) and female (N = 56) participants aged 18 to 51 years (M = 31.56, SD = 8.00) were recruited to complete a questionnaire containing Mach IV Scale (Christie & Geis, 1970) and Intimacy Attitude Scale-Revised (Amidon, Kumar, & Treadwell, 1983). The regression analysis has revealed that Machiavellianism is a reliable predictor of the intimacy attitude of an individual, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Intimacy attitude was measured using the Intimacy Attitude Scale-Revised (IAS-R; [59]). Previous studies have found the IAS-R to be a valid instrument which is highly correlated with constructs of positive and negative intimacy within interpersonal relationships [60]. Correlation equals the components of intimacy attitude [61].…”
Section: Instrumentsmentioning
confidence: 99%
“…Intimacy attitude was measured using the Intimacy Attitude Scale-Revised (IAS-R; [59]). Previous studies have found the IAS-R to be a valid instrument which is highly correlated with constructs of positive and negative intimacy within interpersonal relationships [60]. Correlation equals the components of intimacy attitude [61].…”
Section: Instrumentsmentioning
confidence: 99%
“…Its values range from 0 to 1, where I-CVI > 0.79 indicates that the item is relevant; 0.70–0.79, the item needs revisions, and if < 0.70, the item is eliminated [ 31 ]. The Average Scale-level CVI (S-CVI/Ave) was calculated by taking the sum of the I-CVIs divided by the total number of items [ 32 ]. A S-CVI/Ave ≥ 0.9 show excellent content validity [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…For instance, these employees are more likely to steal (Fehr et al, 1992;Harrell & Hartnagel, 1976), are economically opportunistic and less cooperative (Sakalaki et al, 2007), have lower job satisfaction and higher turnover (Fehr et al, 1992;Wilson et al, 1996), engage in unethical and counterproductive work behaviours (Kish-Gephart et al, 2010;O'Boyle et al, 2012). Furthermore, Machiavellians place little importance on establishing close, intimate relationships, but these relationships do provide Machiavellians with opportunities for emotional manipulation, such as coercion and pleasure induction, and subsequent reward (Lyons & Aitken, 2010;Brewer et al, 2014, Lo & Ng, 2019. All in all, increasing attention has been drawn towards the study of Machiavellianism in recent years due to its prominence in subclinical populations and influence on psychological adjustment (McHoskey, 1999;Martin et al, 2012).…”
Section: Machiavellianismmentioning
confidence: 99%